2015
DOI: 10.4081/ija.2015.640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing density and nitrogen top-dress fertilisation on growth and yield of chia (Salvia hispanica L.) in a Mediterranean environment: first results

Abstract: The demand for sources of nutraceuticals has led to the rediscovery and diffusion of traditional crops such as chia (Salvia hispanica L.), whose leaves and fruits are rich in W3 fatty acids and anti-oxidants. Chia originates in Central America but it is rapidly expanding to new areas. A field experiment conducted at Atella in Basilicata (Southern Italy) was set up to test the response of chia to N top-dress fertilisation (0 and 20 kg ha -1 ) and to sowing density (D1=125, D2=25, D3=8 and D4=4 plants m -2 ) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 7 publications
8
37
2
1
Order By: Relevance
“…In Paraguay yields of 1600 kg ha -1 were reported (Bochicchio et al, 2015), while in the state of Jalisco, Mexico, the main productive zone of chia in this country, mean yields of 1200 kg ha -1 were obtained. In our study, the yields of sowing dates F1 and F2 (between 4 January and 4 February) in CH were systematically and significantly superior to those of VA (Figure 4).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In Paraguay yields of 1600 kg ha -1 were reported (Bochicchio et al, 2015), while in the state of Jalisco, Mexico, the main productive zone of chia in this country, mean yields of 1200 kg ha -1 were obtained. In our study, the yields of sowing dates F1 and F2 (between 4 January and 4 February) in CH were systematically and significantly superior to those of VA (Figure 4).…”
Section: Discussionmentioning
confidence: 89%
“…Chia grows naturally in tropical and subtropical environments; it is optimally established from 400 to 2500 m a.s.l., but conditions below 200 m elevation are not adequate for its cultivation (Orozco et al, 2014). It is intolerant to freezing in all development stages (Lobo et al, 2011;Bochicchio et al, 2015). Its minimum and maximum growth temperatures are 11° and 36 °C, respectively, with an optimum range of 16-26 °C (Ayerza and Coates, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To date, scientific literature on crop management techniques, physiological aspects and agronomic characterization of chia is generally quite scarce, even more so for the production of chia outside of its Mesoamerican origin [8][9][10][11]. In regard to reported sowing densities in the literature, Bochicchio et al [12] stated that growth and yield of chia were highest at sowing densities of 125 plants m -2 which is contrary to Bilalis et al [13] who stated that chia growth was not affected by sowing rate. In terms of quality traits, Bilalis et al [13] showed that the crude protein of chia significantly increased as sowing rates increased.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to sowing density and row spacing, nitrogen fertilization plays a critical role concerning seed yield and seed quality traits. It was shown by Bochicchio et al [12] that N-top-dressing had a negative effect on chia seed yields whereas Bilalis et al [13] reported that chia growth was not affected by fertilization. An assessment of optimized nitrogen fertilization is necessary in order to evaluate the direct effects on plant maturity, seed yield, and protein content, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In preColumbian period, chia seeds were one of the four main components in the diet of Mesoamerican civilizations (Bochicchio et al, 2015). Currently, it has been rediscovered (Ayerza and Coates, 2009) and received remarkable attention due to its exceptional nutritional value (Borneo et al, 2010;Ixtaina et al, 2011).…”
Section: Innovative Crops: General Information and First Results Of Tmentioning
confidence: 99%